Exploring modular architecture for nano satellite and opportunity for developing countries - Rhaman, Md. Khalilur; Monowar, M. I.; Shakil, Shifur Rahman; Kafi, A. H.; Antara, R. S I (© 2015 Institute of Physics Publishing, 2017)
This conference paper was presented in the International Conference on Geological, Geographical, Aerospace and Earth Sciences 2014, AeroEarth 2014; Discovery Kartika Plaza HotelKuta, Bali; Indonesia; 11 October 2014 through 12 October 2014 [© 2015 Institute of Physics Publishing] The conference paper's definite version is available at: http://dx.doi.org/10.1088/1755-1315/23/1/012017